Dissolved polycyclic aromatic hydrocarbons (PAHs-d) in response to hydrology variation and anthropogenic activities in the Yangtze River, China. (15th January 2023) - Shang, Nana; Wang, Chuan; Kong, Jijie; Yu, Heyu; Li, Jianhong; Hao, Weiyue; Huang, Tao; Yang, Hao; He, Huan; Huang, Changchun
Abstract: Owing to their bioavailability and toxicity, the dissolved polycyclic aromatic hydrocarbons (PAHs-d) loaded in rivers are harmful to both inland and marine ecosystems. Thus, exploring the changes in PAHs-d levels and sources is important for controlling PAHs pollution. In this study, the concentration of PAHs-d in the mainstream of the Yangtze River during dry and wet seasons was investigated and the source was analyzed using the positive matrix factorization (PMF) model to assess the response of PAHs-d to hydrological and anthropogenic activities changes. The concentration of PAHs-d in the wet season (166.2 ± 52.51 ng/L) was significantly higher than that in the dry season (89.05 ± 20.89 ng/L) (ANOVA, P  < 0.001), and the sampling sites with high pollution were mainly distributed in the downstream urban agglomeration. Herein, 2–3 rings were identified to play a dominant role in the composition of PAHs-d. Compared with the dry season, the proportion of the low molecular weight (LMW) PAHs-d were relatively depleted and the high molecular weight (HMW) PAHs-d were accumulated in the wet season. Coal and coke combustion were identified as the main sources of PAHs-d (65.9% in the dry season and 59.2% in the wet season), followed by vehicle emissions, petroleum sources, and biomass combustion. Owing to the change in energy consumption structure and climate characteristics, the sources of PAHs-d displayed seasonal variation and spatial heterogeneity. Further, flow was identified as the most important factor affecting PAHs-d in the hydrological parameters. Increases of flow, pH, and SPM decreased the proportion of LMW PAHs-d, and increased that of HMW PAHs-d. The increase in anthropogenic activities intensified the residual levels of 2-3rings and 5–6 rings in water, but had no significant impact on the levels of 4 rings. Highlights: Dissolved PAHs in the Yangtze River were studied by using 0.7 μm filter. PAHs-d residual levels and structures displayed seasonal changes and spatial heterogeneity. PAHs-d in the Yangtze River mainly generated from coal and coke combustion. Flow accelerated the accumulation of PAHs-d in river. Anthropogenic activities had the most significant impact on 2–3 ring PAHs-d.